Predominance of intrinsic mechanism of resting heart rate control and preserved baroreflex sensitivity in professional cyclists after competitive training - Ferreira Azevedo, L.; Perlingeiro, P.; Tessariol Hachul, D.; Gomes-Santos, I. L.; Tsutsui, J. M.; Negrao, C. E.; De Matos, L. D. N. J. (PLOS ONE, 2016)
Different season trainings may influence autonomic and non-autonomic cardiac control of heart rate and provokes specific adaptations on heart`s structure in athletes. We investigated the influence of transition training (TT) and competitive training (CT) on resting heart rate, its mechanisms of control, spontaneous baroreflex sensitivity (BRS) and relationships between heart rate mechanisms and cardiac structure in professional cyclists (N = 10). Heart rate (ECG) and arterial blood pressure (Pulse Tonometry) were recorded continuously. Autonomic blockade was performed (atropine—0.04 mg.kg-1; esmolol—500 µg.kg-1 = 0.5 mg). Vagal effect, intrinsic heart rate, parasympathetic (n) and sympathetic (m) modulations, autonomic influence, autonomic balance and BRS were calculated. Plasma norepinephrine (high-pressure liquid chromatography) and cardiac structure (echocardiography) were evaluated. Resting heart rate was similar in TT and CT. However, vagal effect, intrinsic heart rate, autonomic influence and parasympathetic modulation (higher n value) decreased in CT (P=0.05). Sympathetic modulation was similar in both trainings. The autonomic balance increased in CT but still showed parasympathetic predominance. Cardiac diameter, septum and posterior wall thickness and left ventricular mass also increased in CT (P<0.05) as well as diastolic function. We observed an inverse correlation between left ventricular diastolic diameter, septum and posterior wall thickness and left ventricular mass with intrinsic heart rate. Blood pressure and BRS were similar in both trainings. Intrinsic heart rate mechanism is predominant over vagal effect during CT, despite similar resting heart rate. Preserved blood pressure levels and BRS during CT are probably due to similar sympathetic modulation in both trainings.